Study guides

☆☆

Q: What is m plus 4n plus 3m-6n?

Write your answer...

Submit

Still have questions?

Related questions

n-2m

4 + 4n - 12 = 4n - 8

4n + 5

It is an expression that can be simplified to -4n-1

3n + 2n = 7 + 4n 5n = 7 + 4n 5n - 4n = 7 n = 7

If 7m = 4n+2 and 7m+2 = 8 m = 6/7 and n = 1

8m + (4n - 6m) + 9n =8m + 4n - 6m + 9n =(8m - 6m) + (4n + 9n) =2m + 13n

5m3 + 4n is an algebraic expression.

4n + 30 = 2(2n + 15)

15m + 4n - 5m + 9n = 10m + 13n

3 + 3n = 9 + 2n + 4n n = -2

3n

4n + 3 = 15 4n +3 - 3 = 15 - 3 4n = 12 4n/4 = 12/4 n = 3

4n+13=1 -13 -134n=-12/4 /4n=-3

(4n + 1)*(2n + 6) = 8n2 + 26n + 6

5n-2+2=4n 5n=4n n=0

n = 1 7n + 6n - 5 = 4n + 4 13n - 5 = 4n + 4 13n - 4n - 5 = 4n - 4n + 4 9n - 5 = 4 9n -5 + 5 = 4 + 5 9n = 9 n = 1

it equals -4n

4n

y

4n

Fihd

1

4n-8=3n+2 4n=3n+2+8 4n=3n+10 4n-3n+10 n=10 N = 10

7n + 2 = 4n + 17Subtract 2 from each side:7n = 4n + 15Subtract 4n from each side:3n = 15Divide each side by 3:n = 5